KMUT – Project Management Toolbox - Quade, Stefanie; Birkenkrahe, Marcus; Habermann, Frank (International Journal of Emerging Technologies in Learning (iJET), 2013)
Small and medium-sized enterprises (SMEs) are increasingly dealing with international projects and distributed (sometimes even virtual) teams. Consequently, they are looking for project management (PM) tools which fit their respective needs regarding communication and collaboration. Unfortunately, the majority of the PM software available in the market seems to be oversized for this purpose. Instead most project managers are requesting smart solutions that allow quick implementation without any significant organisational or technical change. Within the research project InterComp SME 2.0 we combine theoretical research and real business to develop hands-on solutions for SMEs. This paper describes an effective approach for a â??PM Toolboxâ? that allows finding the right project tool for a specific project need. The toolbox has been developed in due consideration of user stories gained from business practice, a more detailed SME business survey, a theoretical PM meta model and a market of PM tools. Since the business survey revealed that the readiness to use and test a â??toolboxâ? is highly dependent on the type of user and his or her technical background, we designed the system based on use cases and user typology. As a result, we suggest a framework of open, freely available, easy-to-install, single and multi purpose PM software tools which can be selected solely on a need basis. With this free platform we want to guide practitioners through the tool jungle with the potential to grow into a lively community.